What drives immigration amnesties? - Alessandra Casarico; Giovanni Facchini; Tommaso Frattini (Center for Economic Studies and ifo Institute (CESifo), 2012)
We develop a general model of legal and illegal immigration to understand the basic tradeoffs faced by a government in the decision to implement an immigration amnesty in the presence of a selective immigration policy. We show that two channels play an important role: an amnesty is more likely the more restricted are the occupational opportunities of undocumented immigrants and the less redistributive is the welfare state. Empirical evidence based on a novel panel dataset of legalizations carried out by a group of OECD countries between 1980-2007 broadly supports the role played by the channels identified in our theoretical model.
Keywords: F22; J61; 330; illegal immigration; amnesties; labor market mismatch; welfare state; Illegale Einwanderung; Straffreiheit; Migrationspolitik; Arbeitsmarktflexibilität; Sozialstaat; OECD-Staaten